Assessment of morphological diversity in acid lime (Citrus aurantifolia) genotypes based on floral traits in Jammu region (Current Horticulture, 2024)
The survey was conducted on 70 seedlings of acid lime (Citrus aurantifolia Swingle) genotypes to find out the genetic divergence based on floral characteristics. The data did not reveal much variation in qualitative floral traits. All the seedlings flowered between February and March. The number of days to secondary flowering (163 days) were maximum in JMU-Lait (50) and JMU-Lait(53), and minimum (157 days) in JMU-Log(6), JMU-Log (7), JMU-Kat (14) and JMU-Gura (25). Pedicel length varied from 2.15 to 4.20 mm. The maximum pedicel length (4.20 mm) was in JMU-Sun (63), while minimum (2.15 mm) in JMU-Jib (36). The minimum petal length (11.02 mm) was in JMU-Log (5) and maximum (14.62 mm) in JMU-Uttar (18). The maximum petal width (5.12 mm) was in JMU Nag (68) and minimum (3.19 mm) in JMU-Balli (27). Maximum number of flower buds/inflorescence (8.65) was in JMU-Nag (70) and minimum (3.62) in JMU-Log (4). Anther length (2.25 mm) was maximum in JMU-Nag (67) and minimum in (1.44 mm) in JMU-Log (1).
Keywords: Diversity; Floral characteristics; Genotypes; Indigenous; Morphology